Cyclic Vomiting Syndrome in Children - T.V. Sorokman; S.V. Sokolnyk; O.-M.V. Popelyuk; L.V. Shvygar (Zaslavsky O.Yu., 2016)
Introduction. Cyclic vomiting syndrome (CVS) - is a fairly common disease of unknown etiology that affects children of all age groups and sometimes adult population and refers to the functional disorders of the gastrointestinal tract. Objective: to evaluate the effectiveness of the usage of Rehydron Optim for oral rehydration therapy in children. Materials and methods. The treatment of 40 children aged 3 to 11 years with CVS (15 persons) and primary acetonemic syndrome (25 persons) in the period of acetonemic crisis, including 15 boys and 25 girls, was analyzed. All children were observed in the outpatient department of the Regional children's hospital of Chernivtsi. Diagnosis was established based on anamnesis, clinical and laboratory data. Patients underwent required clinico-biological tests and instrumental examinations. The dynamics of the following syndromes was investigated: pain, vomiting, dehydration and intoxication. Rehydration therapy in all cases was oral with the usage of Rehydron Optim. Results of the study and their discussion. A cyclical vomiting was observed in children with primary acetonemic syndrome with satisfactory condition in attack-free period. Migraine-like headaches prevailed in 36 patients (80 %), and the age of these patients was older than 7 years. Same children had episodes of paroxysmal autonomic failure. Almost all surveyed children had in their family history the risk factors for CVS development. All children had positive dynamics of the main basic clinical manifestations on the background of oral rehydration therapy using Rehydron Optim. Within the 1st day of oral rehydration therapy with Rehydron Optim in children, we have noted a significant decrease in the incidence of lethargy, vomiting, spastic abdominal pain, smell of acetone in the exhaled air (p < 0.05). In children with the I degree of dehydration, clinical signs of dehydration were not seen before the treatment, and children with the II degree had an improvement in their condition, which manifested clinically in the transition of the II degree dehydration into the I degree, which required reduction of rehydration therapy volume. After 48 hours of treatment, the signs of intoxication syndrome (lethargy, drowsiness, headache) were absent in all children. In 80 % of patients, there was a normalization of appetite, the frequency of nausea complaints significantly reduced. On the 5th day of therapy, no children had ketonuria. Conclusions: 1) obviously, there is a correspondence between cyclic vomiting syndrome and primary acetonemic syndrome (cyclic vomiting syndrome = primary acetonemic syndrome); 2) collecting the family history and detailed clinical features of attack-free period is of the significant importance for the diagnosis. The combination of risk factors in family history is one of the criteria for early diagnosis of cyclic vomiting syndrome; 3) during the oral rehydration therapy with the prescription of Rehydron Optim, ketosis completely stops in the vast majority of patients on the 2nd day of treatment; 4) Rehidron Optim has pleasant organoleptic qualities, it is well tolerated by children, and it has an excellent safety profile of application.